PENURUNAN GAS CO PADA SEPEDA MOTOR 2 TAK DENGAN MENGGUNAKAN GIPSUM - Euis Nurul Hidayah (Department of Environmental Engineering-Faculty of Civil, Environmental and Geo Engineering. Institut Teknologi Sepuluh Nopember, Surabaya, 2009)
Air pollution is mostly generated by human activities. One of the causes is transportation. Motor cycles are one of the main sources of carbon monoxide gas emission in Indonesia. The emmited carbon monoxide can cause the decrease of the ability of the body in receiving oxygen. If carbon monoxide is exposed to human for a long time, it may cause bronchitis, emphysema, and lung cancer. One of the best methods to remove of carbon monoxide is by gypsum adsorption. This research used varied gypsum sizes of 5, 10, 15, 20 and 25 cm long, detention times of 30, 60, 90, 120, and 150 minutes, and the holes number of 10 and 20. The results showed that gypsum of 25 cm long, detention time of 150 minutes, hole number of 20 could remove carbon monoxide up to 30.32 %.